Sistem Pendukung Keputusan Penentuan Kelas Unggulan Pada Siswa baru di SMK Negeri Menggunakan Metode SMART (STUDI KASUS: SMK NEGERI 1 BINJAI) - Kiki Angel; Novriyenni Novriyenni; Anton Sihombing (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Excellent class students are students who consist of selected people who have more outstanding abilities when compared to ordinary class students. SMK N 1 Binjai is one of the schools that has implemented a superior class selection where every year the school selects new students to enter the superior class. The selection process is still using a manual system. Selection in this way will take a long time so it is not effective and efficient. This system is designed using the Simple Multi-Attribute Rating Technique (SMART) method where each criterion is given a weight and then calculated using the SMART formula. This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important the criterion is with other criteria. The results of the research are in the form of a recommendation system output for students who will enter the superior class. The benefit of this research is that it provides media for decision-making information for the school to decide which students are eligible to enter the superior class.